Does selective attention demand affect the physiological complexity of postural control in faller community-dwelling older adults? Cognition and postural control in older adults - Alves Silva Lima, Letícia; dos Santos Leal, Iara; Gomes de Alencar, Júlia; Fulgêncio Alves da Silva, Tarcísio; Trombini-Souza, Francis (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: The physiological complexity of postural control during selective attention demand can be used as an innovative method to identify faller community-dwelling older. Objective: To analyze the effect of selective attention on the complexity of postural control in faller community-dwelling older adults. Methods: A total of 57 older adults (60 to 80 years) were divided between the faller group (Fallers n = 21) and the non-faller group (Non-fallers n = 36). An inertial sensor (Physilog® 5, GaitUp, Switzerland) was positioned over the second sacral vertebra to collect the participant’s body sway in the anteroposterior (AP) and mediolateral (ML) directions during the monochromatic and color Stroop test versions. The postural control’s complexity was calculated using MATLAB codes, employing the refined composite multiscale fuzzy entropy method. Statistical Package for Social Sciences was used to analyze the effects of interaction, group, and condition effects using linear mixed models with an alpha of 5%. Results: No significant interaction effects were observed in the AP (F = 0.18; p = 0.66) and ML (F = 0.00; p = 0.99) directions. No group effect was observed in the AP (F = 1.23; p = 0.26) and ML (F = 1.76; p = 0.18) directions. No condition effect was found in the AP (F = 0.06; p = 0.80) and ML (F = 3.54; p = 0.06) directions. Conclusion: Once-only faller community-dwelling older adults did not evidence worse physiological complexity than the non-fallers during selective attention demand in the upright standing posture.